Influence of automobile industrial wastewater on soil quality - Nnaemeka, Ugwu Samson; Chukwuemeka, Anyadike Chinenye; Emmanuel, Echiegu; Achuka, Nwoke Oji; Boniface, Ugwuishiwu (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Reuse of industrial wastewater (effluent) for irrigation purpose is a common practice. However, lack of adequate treatment of the effluent can cause soil deterioration, vegetation destruction and contamination of the aquatic environment. These adverse effects necessitated the study of wastewater irrigation in Emene Industrial Layout, Enugu State, Nigeria. Wastewater and soil samples were collected, analyzed and subjected to Analysis of Variance (ANOVA) for Completely Randomized Design (CRD) at 5% probability level using GENSTAT software. The results obtained from the study were compared with FAO soil and water standards. The wastewater analysis suggested that contamination at the untreated stage was very high and results at the treatment level were within the FAO reuse range. The study also found wide variation in chemical status of industrial wastewater treated soil. Almost all the values for the wastewater treated soil were not within the FAO irrigated soil chemical properties standards. This suggests high re-contamination along the open channel (from non-point sources) before reuse. This calls for proper monitoring and treatment of the industrial effluent prior to irrigation application. Keywords: irrigation, soil quality, contamination, wastewater, automobile industry DOI: 10.3965/j.ijabe.20140706.015 Citation: Ugwu S N, Anyadike C C, Echiegu E, Nwoke O A, Ugwuishiwu B. Influence of automobile industrial wastewater on soil quality. Int J Agric & Biol Eng, 2014; 7(6): 123－128.